Kajian Infrastruktur Transportasi Darat Dalam Pengembangan Wilayah Kecamatan Tongauna Kabupaten Konawe - Juantoro, Eko Efendi; Magribi, La Ode Muhamad; Lakawa, Irwan; Sufrianto, Sufrianto (Sultra Civil Engineering Journal (SCiEJ), 2020)
The development of rural areas from the agricultural base sector in the field of food through land transportation infrastructure is the main focus of this research. The location of the object of research was Tongauna District, Konawe Regency, Southeast Sulawesi Province. which is the background for site selection because the majority of the people in Tongauna are farmers and the Tongauna sub-district is the district with the largest production of lowland rice commodity in Southeast Sulawesi province which can be an agricultural base sector. Land transportation has become a very important media that supports the mobility, connectivity and accessibility of agriculture so as to increase the productivity of leading sectors of agriculture that have an impact on the development of the area of Tongauna District.